Studi Meta Analisis Pengaruh Scientific Approach dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Dr Heri Retnawati; Imam Subarkah (Prodi MPI IAINU Kebumen, 2018)
This study aims to analyze Scientific Approach Learning models intended to improve Learning Outcomes. Scientific Approach is learning process designed in such a way that learners actively construct concepts, laws, or principles through the stages, observing stages, formulating problems, submitting hypotheses, collecting data with various techniques, analyzing data, drawing conclusions, and communicating. In this study the researchers used a meta-analysis method. First, the researcher formulated the research problem, then proceeded to review the existing relevant research for analysis. Data were collected by using a non-test technique by browsing electronic journals through Google Scholar and studying documentation in the library. Twevfe were found through Google Scholar and twoe was found in the library. Based on the analysis of the results, the Scientific Approach learning model can improve Learning Outcomes